Posttraumatic growth among childhood cancer survivors: Associations with ethnicity, acculturation, and religious service attendance. Issue 2 (4th March 2018) - Tobin, Jessica; Allem, Jon-Patrick; Slaughter, Rhona; Unger, Jennifer B.; Hamilton, Ann S.; Milam, Joel E.
ABSTRACT: This study assessed the association between ethnicity, religious service attendance (RSA), and acculturation with posttraumatic growth (PTG) in a diverse sample of 235 childhood cancer survivors (CCS). PTG scores were estimated for each ethnicity, and by level of RSA and acculturation. There was a significant curvilinear relationship (inverted U) between RSA and PTG, such that moderate levels of RSA were associated with the highest PTG scores. Hispanics reported the highest PTG, and both Hispanic and Anglo cultural orientation were significantly positively associated with PTG. CCS with high or low frequency of RSA as well as Hispanic CCS who lack a strong sense of cultural identity may benefit from targeted efforts to promote psychosocial adaptation in the aftermath of cancer.